Normal lymphocyte homeostasis and function in MALT1 protease‐resistant HOIL‐1 knock‐in mice. (19th December 2022) - Skordos, Ioannis; Driege, Yasmine; Haegman, Mira; Kreike, Marja; Staal, Jens; Demeyer, Annelies; Beyaert, Rudi
Abstract : The uniqueness of MALT1 protease activity in controlling several aspects of immunity in humans has made it a very attractive therapeutic target for multiple autoimmune diseases and lymphoid malignancies. Despite several encouraging preclinical studies with MALT1 inhibitors, severe reduction in regulatory T cells and immune‐mediated pathology seen in MALT1 protease‐dead (MALT1‐PD) mice and some, but not all, studies analysing the effect of prolonged pharmacological MALT1 protease inhibition, indicates the need to further unravel the mechanism of MALT1 protease function. Notably, the contribution of individual MALT1 substrates to the immune defects seen in MALT1‐PD mice is still unclear. Previous in vitro studies indicated a role for MALT1‐mediated cleavage of the E3 ubiquitin ligase HOIL‐1 in the modulation of nuclear factor‐κB (NF‐κB) signalling and inflammatory gene expression in lymphocytes. Here, we addressed the immunological consequences of inhibition of HOIL‐1 cleavage by generating and immunophenotyping MALT1 cleavage‐resistant HOIL‐1 knock‐in (KI) mice. HOIL‐1 KI mice appear healthy and have no overt phenotype. NF‐κB activation in T or B cells, as well as IL‐2 production and in vitro T‐cell proliferation, is comparable between control and HOIL‐1 KI cells. Inhibition of HOIL‐1 cleavage in mice has no effect on thymic T‐cell development and conventional T‐cell homeostasis. Likewise, B‐cell development and humoral immune responses are not affected. Together, these data exclude an important role of MALT1‐mediated HOIL‐1 cleavage in T‐ and B‐cell development and function in mice. Abstract : The paracaspase MALT1 plays a key role in controlling aspects of human immunity, making it an attractive therapeutic target for autoimmune diseases and lymphoid malignancies. MALT1 fine‐tunes the development and function of the immune system by cleaving several substrates, including E3 ubiquitin ligase HOIL‐1. However, the contribution of individual MALT1 substrates in the regulation of immune homeostasis is still unclear. Here, by generating and immunophenotyping MALT1 cleavage‐resistant HOIL‐1 knock‐in mice, a team led by Rudi Beyaert demonstrates that MALT1‐mediated HOIL‐1 cleavage is dispensable for T‐ and B‐ cell development and function in mice, ruling out a key regulatory mechanism in lymphocyte homeostasis.